ULUSAL GAZETELERİN ALGI YARATMA İŞLEVİ (16 KASIM 2013 DİYARBAKIR BULUŞMASI HABERLERİ BAĞLAMINDA BİR ANALİZ) - SOLMAZ, ERKAN (Fırat Üniveristesi, 2016)
Teknolojik gelişmelerle birlikte hayatımıza yön veren kitle iletişim araçları, gün geçtikçe etkisini arttırmaktadır. Kitle iletişiminin giderek hız kazandığı günümüz dünyasında, medyanın enformasyon üzerindeki yaptırım gücüde açıkça görülmektedir. Medya iktidar ilişkisi bağlamında, kitlelere iletilen mesajların nasıl bir süreçten geçtiği, ne şekilde aktarıldığı ve hangi etkenlerle oluşturulduğu analiz edilmiştir. Söylemin habere dönüştürülürken işlendiği editöryal süreç ve hedef kitleye yönelik yansıması, "Haber Söylem Çözümlemesi" tekniğine uygun olarak yapılmıştır. Araştırmada ulusal gazetelerin algı yaratma işlevi irdelenmiştir. Ayrıca iletişim kuramlarının ana dayanağı olan siyasi sistemler ile medya arasındaki ilişki yorumlanmıştır. Ulusal gazetelerde ideolojilerin, kitle üzerinde algı oluşturmaya yönelik amaçladığı çıkar ve fayda politikası, oluşturulan hipotezlerle, "16 Kasım 2013 Diyarbakır Buluşması Haberleri" üzerinden açıklanmaya çalışılmıştır. Anahtar Kelimler: Medya, İdeoloji, Söylem, Haber, Algı

Mass media which points the way to our lives along with technological developments lifts its effectiveness day by day. Intoday's world in which mass communication gather pace gradually, the sanction power of media on informatics is seen obviously. In the context of media potential, what kind of processes do the messages which are transmitted to masses go through, in what way they are transferred and with which factors they are formed; are analyzed. Editorial process in which discourse is manipulated while being converted to news and its reflection to the intended population is done in compliance with the "News Discourse Analysis" technique. In this study, the perception creating function of national newspapers is examined. In addition, the relationship between media and political systems which are main supports of communication theories is interpreted. The profit and benefit politics which is aimed by ideologies to create perception on the mass in national newspapers are tried to explain with the developed hypothesis on "16thNovember 2013 Diyarbakır Meeting News". Key Words: Media, Ideology, Discourse, News, Perception
The perception creating function of national newspapers (An analysis in the context of 16thnovember 2013 Diyarbakır meeting news)
Keywords: Gazetecilik; İletişim Bilimleri